The politics of land use planning: gold mining in Cajamarca, Peru - Jeronimo, R.P.; Rap, Edwin; Vos, J. (Elsevier, 2015)
Ecological and Economic Zoning (EEZ) is a Land Use Planning (LUP) methodology that aims at defining separate areas for productive uses and conservation. EEZ is designed as a method that balances different interests and it devises land use policy through stakeholder participation, technical expertise and GIS modelling. The article presents the case study of EEZ in Cajamarca, Peru to analyse the LUP process in a situation of conflicting interests over future land and water use. Cajamarca is a department with rich gold deposits in the headwater catchment area upstream of the city of Cajamarca. During the last decade, rural communities and urban populations have continuously protested against the opening of new open pit mines, as they fear this will affect their water supply. Therefore, the EEZ process became part of a controversy between a powerful pro-mining coalition lead by the central government and a conservation coalition lead by the regional government. We conclude that in these circumstances, LUP cannot, technically or politically, accommodate the different values attributed to the headwater catchment.